Rights in Conflict?: Exploring the Expansion of Victims’ Rights in Light of the Presumption of Innocence - Michelle Coleman (Rights in Criminal Law: Exploring the Role of Individual Entitlements in Criminal Law: Studies on a New Paradigm in Criminal Law and Procedure)
This chapter examines recent calls for the expansion of victims’ rights and discusses how greater participation and protection of victims through the development of new rights helps support a rights-based approach to criminal law. The chapter argues that victims’ rights cannot be expanded in a vacuum. The presumption of innocence is a fundamental right of accused persons and bedrock to ensuring that individuals are not punished or treated as if they are guilty without a conviction. Further it has a very important structural role to play within criminal justice. Because of this, an unexamined increase in victims’ rights can cause accused people to be treated as if they are guilty either by the court or wider community. Taking a human rights-based approach to criminal justice would improve victims’ rights to identification and participation, however it would require a restructure of criminal justice processes and a redetermination of the goals of trial.